Safety and efficacy of a feed additive consisting of copper(II)‐betaine complex for all animal species (Biochem Zusatzstoffe Handels‐ und Produktionsges. mbH). (22nd February 2023) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Durjava, Mojca; Kouba, Maryline; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, the EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP Panel) was asked to deliver a scientific opinion on the safety and efficacy of a copper(II)‐betaine complex as nutritional feed additive for all animal species. Based on the results of a tolerance study carried out in chicken, the FEEDAP Panel concluded that the additive is safe for chickens for fattening when used up to the current maximum authorised levels of copper in feed; this conclusion was extrapolated to all animal species and categories at the respective maximum copper levels in complete feed authorised in the European Union. The FEEDAP Panel concluded that the use of the copper(II)‐betaine complex in animal nutrition at the maximum copper levels authorised for the animal species poses no concern to the safety of consumers. Regarding the safety for the environment, the use of the additive in feed for terrestrial animals and land‐based aquaculture is considered safe under proposed conditions of use. The data available do not allow the conclusion to be made on the safety of the additive for marine sediment when it is used in sea cages. The additive is not a skin irritant, but it is an irritant to the eyes. Due to the traces of nickel, the additive is considered to be a respiratory and skin sensitiser. The Panel could not conclude on the efficacy of the product.